Periodo reproductivo y talla de madurez masiva del camarón de roca Sicyonia penicillata (Decapoda: Sicyoniidae) en Bahía Kino, Sonora, México - López-Martínez, J (1999)
The reproductive pattern of the rock shrimp (Sicyonia penicillata) was studied from January through December (1996) by sampling from boats twice a month (commercial shrimp fleet and one research cruise). Reproductive activity begins at 25 mm of tail length, but massive maturity or critical size is 55 mm of tail length. Mature organisms were found year round, but recruitment pattern analysis indicates that massive reproduction is from August through January; a second, less intense reproductive peak, occurs in March-April. Results are coincident with the gonadical maturity analysis. A migration pattern of juveniles towards shallow areas of Bahía Kino is suggested. Key words: Shrimp,